When the Dark Shadow of Virtual Reality Intrudes into the Real World: A Study of Ursula Poznanski’s Young Adult Novel, Erebos - Sriwarakan, Siriporn (Journal of Letters, 2021)
This paper studies Ursula Poznanski’s Erebos (2010), a German young adult novel, in terms of the concerns it raises about the dangers of and solutions to computer game addiction among young adults. The novel shows the dominance of the computer game “Erebos,” which uses artificial intelligence (AI) to process the interests and desires of its players. These players are shown attaching themselves to their virtual selves so much that they deny their real-world selves, and are then manipulated by the Erebos AI to commit acts of violence. On the other hand, the novel reveals that such obsession can be solved when the protagonist, one of the addicted gamers, learns to recognize the violence caused by this computer game after he comes across a violent incident in which some addicted players attack Erebos’ enemies in the real world. Such presentation shows that the novel has a hopeful view towards computer game dominance, that the problem can be solved through the perception of violent experience resulting from domination of a computer game, and through learning that one should not resort to violence to solve problems.